Timeless running wisdom - Benyo, Richard (Human Kinetics, 2011)
You run because you like the way it makes you feel in its best moments. You run with a goal of success and satisfaction. Wouldn't you like to tap into those feelings more often? In Timeless Running Wisdom, longtime runner and author Rich Benyo takes you on a journey spanning the trends of the sport and the approaches, concepts, and methods that have bred success and satisfaction across generations of runners. Discover how to embrace simplicity; change up routes, distances, and terrains; keep your running in proportion to the rest of your life; and create your own adventure runs. It's all here-